Shergottite Northwest Africa 6963: A Pyroxene‐Cumulate Martian Gabbro. Issue 7 (25th July 2018) - Filiberto, Justin; Gross, Juliane; Udry, Arya; Trela, Jarek; Wittmann, Axel; Cannon, Kevin M.; Penniston‐Dorland, Sarah; Ash, Richard; Hamilton, Victoria E.; Meado, Andrea L.; Carpenter, Paul; Jolliff, Brad; et al.
Abstract: Northwest Africa (NWA) 6963 was found in Guelmim‐Es‐Semara, Morocco, and based on its bulk chemistry and oxygen isotopes, it was classified as a Martian meteorite. On the basis of a preliminary study of the textures and crystal sizes, it was resubclassified as a gabbroic shergottite because of the similarity with terrestrial and lunar gabbros. However, the previous work was not a quantitative investigation of NWA 6963; to supplement the original resubclassification and enable full comparison between this and other Martian samples; here we investigate the mineralogy, petrology, geochemistry, quantitative textural analyses, and spectral properties of gabbroic shergottite NWA 6963 to constrain its petrogenesis, including the depth of emplacement (i.e., base of a flow versus crustal intrusion). NWA 6963 is an enriched shergottite with similar mineralogy to the basaltic shergottites but importantly does not contain any fine‐grained mesostasis. Consistent with the mineralogy, the reflectance (visible/near‐infrared and thermal infrared) spectrum of powdered NWA 6963 is similar to other shergottites because they are all dominated by pyroxene, but its reflectance is distinct in terms of albedo and spectral contrast due to its gabbroic texture. NWA 6963 represents a partial cumulate gabbro that is associated with the basaltic shergottites. Therefore, NWA 6963 could represent a hypabyssal intrusive feeder dike system for the basaltic shergottites that erupted on the surface. Plain Language Summary: This study investigates a new meteorite from Mars, which has different properties than previous Martian meteorites. Specifically, this rock has large crystals that likely formed as the magma ponded in the crust instead of erupting as a lava flow. On Earth, 10 times more magma gets stuck in the crust than erupts on the surface; therefore, we would expect something similar on Mars—yet this rock is the first example of an intrusive magma on Mars. This work shows that this meteorite possibly represents the feeder dike system that fed the lava flow represented by the other shergottite meteorites. Key Points: Shergottite Northwest Africa 6963 represents a pyroxene‐cumulate Martian gabbro NWA 6963 could represent a hypabyssal intrusive feeder dike system for the basaltic shergottites that erupted on the surface